Kunci Sukses Timnas Bola Basket Putra Sea Games 2021 Vietnam (Literature Review) - Khory, Fifukha Dwi; Jr, Procopio B. Dafun; Rizky, Muhammad Yanuar; Hariyanto, Agus (Jurnal Porkes, 2022)
The purpose of this research is as the main study material. on the achievements of the Men's Basketball National Team in winning a gold medal at the 2022 Sea Games. The study in this research is the keys to success in the Men's Basketball National Team as seen from nursery, coaching and organizational management at Perbasi. So it is hoped that the results of this research can be used as one of the study materials to develop basketball in Indonesia. This research was conducted at the 2022 sea games multi-event event which took place on May 16-22 2022. The data source used is secondary data from the statistical results of the 2022 sea games basketball competition on the website https://www.sofascore.com/ id/philippines-indonesia/Zgxsbhx, secondary data used for field goal match analysis, 2 points made, 3 point field goals, free throws, total rebounds, assists, steals, blocks, turn overs, and points from turn overs. the results of the analysis regarding the statistical analysis of the final sea games basketball match which has been discussed in the discussion, the conclusion in this study states that. There are 3 winning factors, namely field goals, turnover and assists.